Social Pathology in Penyalin Cahaya Film: A Study of Sociology of Literature - Rusli, Herman; Mukhlis; Diba, Wulan Farah (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Social pathology often occurs in everyday life. Social pathology as a deviation of social behavior occurs due to various factors. These symptoms can arise from individual or group factors. Social deviations often also appear in literature and films. One of the films that most addresses social pathology is "Penyalin Cahaya" directed by Raphael Wregas Bhanuteja. The study of social pathology in films is very important to be examined because films are often used as examples by the audience. This study aims to examine social pathology in the film "Penyalin Cahaya". The key question to be answered is what forms of social pathology are found in the film "Penyalin Cahaya". This research uses a qualitative descriptive approach. The data source used is the film "Penyalin Cahaya" which has been nominated for the 2022 Piala Citra. The research data are dialogues and scenes that contain forms of social pathology. Data collection techniques include observation, observation, and documentation. The results show that (1) social pathology in the film "Penyalin Cahaya" occurs in the form of mental disorders, criminality, corruption, alcohol, drugs, and pornography; (2) the depiction of social pathology in this film is through dialogues, scenes, and the portrayal of criminal events (data theft, illegal thesis sales, violence, obstruction of justice), corruption, alcohol (binge drinking), drugs (marijuana), and pornography (sexual harassment). It can be concluded that this film contains many social deviations shown through dialogues and scenes. These social pathologies serve as education for every viewer and the general public.